The Influence of Brand Equity on Consumer Interest in Buying Xiaomi Smartphones - Sioaji Yamawati; Ni Luh Putu Indiani (Warmadewa Management and Business Journal (WMBJ), 2019)
The dramatic increase in Xiaomi smartphone sales in Indonesia raised research interest, especially related to factors encouraging consumer interest in purchasing the Xiaomi smartphone. Through empirical studies, it concluded that an important factor influenced consumer buying interest was brand equity consisting of brand awareness, brand association, quality perception, and brand loyalty. This study aims to analyze the influence of brand awareness, brand association, quality perception, and brand loyalty on consumer interest in purchasing a Xiaomi smartphone. This study is designed using quantitative approach in which the data collection is conducted through surveys using questionnaires. The study population is the Denpasar people who plan to purchase a smartphone in the near term. Samples were taken using accidental sampling method that is people who visited smartphone stores in Denpasar. The questionnaire was used to collect data, then analyzed using multiple linear regression analysis. The result showed that brand awareness, brand association, quality perception, and brand loyalty have a positive and significant influence on consumers' interest in buying a Xiaomi smartphone. Brand awareness, brand association, and quality perception can be enhanced by intensive marketing communication in various media emphasizing symbol, logo, product excellence, and quality excellence. This statement needed to be supported by consumer reviews that are in line, therefore customer database is necessary to encourage satisfied customers to write positive reviews in online media.